Improving amateur indoor rock climbing performance using a changing criterion design within a self-management program - Furlonger, B. E.; Oey, A.; Moore, D. W.; Busacca, M.; Scott, D. (The Sport Journal, 2017)
Despite the popularity of indoor rock climbing there is little information on how amateur climbers can improve their performance. A single-case experimental design with baseline, intervention, and post intervention phases was conducted using a changing criterion design within a self-management program. Discrete exercise training and combined training methods were trialled, with the effects of both on actual rock climbing compared. All discrete exercises improved over baseline; Powerball grip 45%, open-handed pull-ups by 50% and multi-stage fitness 35%. There was, however, no observable improvement in climbing performance. In contrast combined training led to a 40% improvement in climbing performance. For amateurs wishing to improve their recreational indoor rock climbing ability, practicing the task holistically rather than by training discrete skills in isolation may prove to be more effective.